2008
DOI: 10.3171/jns/2008/108/6/1122
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial hemorrhage associated with stent-assisted coil embolization of cerebral aneurysms: a cautionary report

Abstract: The necessity of dual antiplatelet therapy in the use of stent-assisted coil embolization increases the risk of intracranial hemorrhage and possibly rebleeding from a ruptured aneurysm. This heightened risk must be recognized when contemplating the appropriate therapy for a cerebral aneurysm and when considering the placement or manipulation of a ventricular catheter in a patient receiving dual antiplatelet therapy. Further study of intracranial procedures in patients receiving dual antiplatelet therapy is ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
93
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(95 citation statements)
references
References 20 publications
2
93
0
Order By: Relevance
“…Second, the risk of the vessel stenosis or the formation of thrombosis must also be considered. Because the stent can induce neointimal hyperplasia, thrombosis or occlusion of the smaller arteries, the necessity of dual antiplatelet therapy in conjunction with stent-assisted coil embolization increases the risk of intracranial hemorrhage and possibly rebleeding from a ruptured aneurysm 25) . The balloon-assisted technique, in which a non-detachable balloon is advanced into the parent artery and inflated to occlude the neck of aneurysm, stabilizes the microcatheter in the aneurysm during coil delivery and prevents the coil impinging on the parent artery.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the risk of the vessel stenosis or the formation of thrombosis must also be considered. Because the stent can induce neointimal hyperplasia, thrombosis or occlusion of the smaller arteries, the necessity of dual antiplatelet therapy in conjunction with stent-assisted coil embolization increases the risk of intracranial hemorrhage and possibly rebleeding from a ruptured aneurysm 25) . The balloon-assisted technique, in which a non-detachable balloon is advanced into the parent artery and inflated to occlude the neck of aneurysm, stabilizes the microcatheter in the aneurysm during coil delivery and prevents the coil impinging on the parent artery.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, in the context of anticoagulant or antiplatelet therapy, ventriculostomy should be considered as a significant risk factor for hemorrhagic complications. 28,31 Antiplatelet agents inhibit the coagulation of bleeding from vessels injured by EVD, making the hemorrhage size larger. Kim et al 19 showed the hemorrhage risks associated with SAC.…”
Section: Discussionmentioning
confidence: 99%
“…However dual antiplatelet therapy is necessary to prevent thromboembolism after stent placement and may increase the risk of intracranial hemorrhage or rebleeding from a ruptured aneurysm. 50 Because a ruptured AICA aneurysm is often accompanied by intraventricular hemorrhages, an intracranial procedure such as EVD should be carefully performed after dual antiplatelet therapy. In this study, 1 patient with stent-assisted coiling required EVD, which was performed without intracranial hemorrhage.…”
Section: Discussionmentioning
confidence: 99%